Pengobatan Penyakit Diare (Kolibasilosis) pada Babi dalam Upaya Meningkatkan Produkivitas Ternak di Desa Sudimara, Tabanan - I.G.K. Suarjana; K. Tono P.G; N.K. Suwi; I.A.P. Apsari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
Have performed community service on Treatment of Diarrhea (Colibacillosis) In Pigs In Effort Improving Livestock Productivity in Sudimara village, Tabanan. This dedication is aimed at providing knowledge to the public about how to manage pigs intensively, ways of prevention and eradication of the disease in pigs kolibasilosis effectively and efficiently so as to maximize their production. Methods of service in the form of the action from home to home, especially to farmers whose pigs diarrhea, held a therapeutic action in the form of antibiotics, anthelmintic, vitamins and minerals and to provide education on how to prevent diarrhea in pigs. The results obtained as follows: the team held a service from house to house on seven breeder pigs reportedly suffering from diarrhea. Pig diarrhea ranging from 1-3 months of age and the amount treated as many as 65 individuals. Based monitoring and reporting team community service founded that on the seventh day after the treatment was given these pigs had not diarrhea or healthy.